2017
DOI: 10.1055/s-0037-1603756
|View full text |Cite
|
Sign up to set email alerts
|

Unusually High Rate of Early Failure of Tibial Component in ATTUNE Total Knee Arthroplasty System at Implant–Cement Interface

Abstract: A novel design total knee arthroplasty (TKA) system has been introduced to improve patient outcomes and increase longevity. However, we have encountered a high rate of debonding of tibial implant-cement interface. In addition, multiple reports have been filed in Manufacturer and User Facility Device Experience database (MAUDE) with the same mechanism of failure. Therefore, we evaluated: clinical, radiographic, and intraoperative findings of patients who received this system and required a revision surgery, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…One paper reported more revisions supposedly related to cement implant debonding for the ATTUNE, 15 however this was a case series without reporting the size of the series in which the findings were made, making it of limited scientific value. 35 , 36 Potential problems with cement adherence to the undersurface of the tibial plateau have also been presented by others, 37 , 38 and for other modern tibial components of TKA implants.…”
Section: Discussionmentioning
confidence: 96%
“…One paper reported more revisions supposedly related to cement implant debonding for the ATTUNE, 15 however this was a case series without reporting the size of the series in which the findings were made, making it of limited scientific value. 35 , 36 Potential problems with cement adherence to the undersurface of the tibial plateau have also been presented by others, 37 , 38 and for other modern tibial components of TKA implants.…”
Section: Discussionmentioning
confidence: 96%
“…Future analysis is required in order to better address the role of both the design and cement features in order to understand fully the phenomenon of debonding at the implant-cement interface observed in a previous study. 17…”
Section: Discussionmentioning
confidence: 99%
“…Recently, early aseptic failures at the implant-cement interface in the Attune TKA system (DePuy, Warsaw, Indiana) were reported in a retrospective study without a control group; 17 the authors found a high rate of early aseptic tibial loosening. The study was based on data from the Manufacturer and User Facility Device Experience (MAUDE) database, 18 which is of limited use because it is a self-reported manufacturer database.…”
Section: Introductionmentioning
confidence: 99%
“…Although superior surface technology that minimizes potential allergic reactions and enhances wear characteristics is promising, the surgical community must consider more than just potential wear characteristics such as adhesion. Second, there are other noncoated implants currently on the market with early tibial tray failure that have gone through geometric surface modification to enhance cement adhesion that may need closer scrutinizing, although none have shown a sustained failure rate similar to this report [26] .…”
Section: Discussionmentioning
confidence: 65%